Characterisation of two new radiochromic gel dosimeters TruView™ and ClearView™ in combination with the vista™ optical CT scanner: A feasibility study. (August 2018) - Colnot, J.; Huet, C.; Gschwind, R.; Clairand, I.
Highlights: A characterisation of two commercialised gel dosimeters is presented. Linear dose response and good intra-batch uniformity are observed. Dose errors are induced by optical scanning, different protocols are investigated. Abstract: Purpose: This study aims at characterising the properties of TruView™ and ClearView™ two new gel dosimeters (Modus Medical Devices Inc.) and at studying the feasibility of relative dosimetry using these dosimeters and the Vista™ Optical CT scanner to accurately evaluate dose. Methods: In this work, we investigated key dosimetric aspects (dose response, energy and dose rate dependence) and stability of these radiochromic gels initiated in preliminary works (Huet et al., 2017; Colnot et al., 2017) using spectrophotometric measurements. Moreover, by mean of optical CT scanning (Vista™), their performances to measure relative depth dose (PDD) and cross profiles were analysed. Results: TruView™ and ClearView™ present a linear dose response up to 20 Gy and up to 80 Gy respectively, independent of both photon beam energy (4–18 MV) and dose rate (up to 9.9 Gy/min) (Huet et al., 2017; Colnot et al., 2017). ClearView™ response proves to be stable for a week post-irradiation and uniform within the batch whereas TruView™ presents an unstable but uniform response. Optical CT scanning generates errors due to stray light that need to be corrected in order to use these gels; ClearView™ scanning particularly requires important precautions. After corrections, those gels used in combination with the Vista™ scanner show promising spatial and dosimetric precision (dose difference <5%). Finally, TruView™ is reusable and presents excellent reproducible response (maximum 3% difference) and the ClearView™ dosimeter presents good spatial stability (0.5% difference after 6 days). Conclusion: This study provides important knowledge about two gel dosimeters presenting interesting dosimetric properties. A study is ongoing to benchmark those promising candidates for clinical dose verification.